Estrategias Educativas Inclusivas y Participación Activa en Estudiantes de Sexto Grado en una Escuela Primaria de Mexicali, Baja California - Ericka Arlín Cárdenas Ramos; César David Eizalde González; Gendi del Rosario Leyva Castro (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
This study aimed to analyze the influence of implementing inclusive educational strategies on the active participation of sixth-grade students at 14 de marzo de 1903 Elementary School in Mexicali, Baja California, during the 2025–2026 school year. A quantitative approach was employed using a non-experimental, correlational, and cross-sectional research design. The study included 72 students who completed a 15-item Likert-scale questionnaire. The instrument demonstrated high internal consistency, with a Cronbach's alpha coefficient of α = .931, and the data were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings revealed a positive relationship between inclusive educational strategies and students' active participation. Collaborative learning, peer interaction, and respectful learning environments promoted greater student engagement and strengthened their sense of belonging. The study concludes that implementing inclusive educational strategies is an effective pedagogical resource for fostering active participation and strengthening more inclusive and equitable educational practices in primary education.